2010
DOI: 10.1371/journal.pntd.0000575
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis at the Crossroad of Phylogenetics and Paleopathology

Abstract: The origin of syphilis is still controversial. Different research avenues explore its fascinating history. Here we employed a new integrative approach, where paleopathology and molecular analyses are combined. As an exercise to test the validity of this approach we examined different hypotheses on the origin of syphilis and other human diseases caused by treponemes (treponematoses). Initially, we constructed a worldwide map containing all accessible reports on palaeopathological evidences of treponematoses bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 49 publications
4
55
0
7
Order By: Relevance
“…However, evolutionary order with respect to TPA and TPE strains cannot be unambiguously inferred from this analysis (Mulligan et al, 2008), especially in the light of genome decay identified in T. paraluiscuniculi (Šmajs et al, 2011), which suggests that T. paraluiscuniculi is a descendant of an ancestor of pallidum and pertenue strains rather than the opposite. Measurement of evolution rate in treponemes and its comparison with paleopathological evidence and with evolution rates of other bacteria is consistent with the divergence of syphilis from other human treponematoses 5 - 16.5 thousand years ago (de Melo et al, 2010). …”
Section: Origin Of Syphilis and Evolution Of Pathogenic Treponemessupporting
confidence: 67%
See 1 more Smart Citation
“…However, evolutionary order with respect to TPA and TPE strains cannot be unambiguously inferred from this analysis (Mulligan et al, 2008), especially in the light of genome decay identified in T. paraluiscuniculi (Šmajs et al, 2011), which suggests that T. paraluiscuniculi is a descendant of an ancestor of pallidum and pertenue strains rather than the opposite. Measurement of evolution rate in treponemes and its comparison with paleopathological evidence and with evolution rates of other bacteria is consistent with the divergence of syphilis from other human treponematoses 5 - 16.5 thousand years ago (de Melo et al, 2010). …”
Section: Origin Of Syphilis and Evolution Of Pathogenic Treponemessupporting
confidence: 67%
“…The genetic distance between TPA and TPE strains appears to be inconsistent with a recent emergence of syphilis in the 15 th century and TPA strains appear to be at least several thousand years old (de Melo et al, 2010; Gray et al, 2006). However, one cannot exclude a very rapid adaptation of a parasite to its host under the right circumstances.…”
Section: Origin Of Syphilis and Evolution Of Pathogenic Treponemesmentioning
confidence: 94%
“…Analyses based on the mutation rates of genomic sequences suggest that the causative agents of yaws and venereal syphilis diverged several thousand years ago from a common progenitor originating in Africa 2 . These estimates argue against the so-called Columbian hypothesis — the notion that shipmates of Christopher Columbus imported a newly evolved spirochete causing venereal syphilis from the New World into Western Europe in the late 15 th century 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Ausgangspunkt wäre das Gebiet des heutigen Guyana gewesen. Einiges spricht für die Hypothese, dass die Syphilis bereits nach der ersten Besiedlung Amerikas, also 16.500 bis 5000 Jahre vor der heutigen Zeit, aufgetreten ist [12]. Es ist jedoch nach wie vor nicht geklärt, wo der Ursprung der Syphilis zu suchen ist, in oder außerhalb Amerikas?…”
unclassified